Systematic analyses of Ophiocordyceps ramosissimum sp. nov., a new species from a larvae of Hepialidae in China - Wen, Ting-Chi; Xiao, Yuan-Pin; Li, Wen-Jing; Kang, Ji-Chuan; Hyde, Kevin D. (Phytotaxa, 2014)
A new species, Ophiocordyceps ramosissimumsp. nov., is described and illustrated. It was associated with larvae of Phassus nodus (Hepialidae) collected from Xuefeng Mountains, Hunan Province, China. It differs from similar species in having branched stromata without a sterile apex, superficial ascomata, and very wide asci and ascospores and in its occurrence on Phassus nodus in living roots or trunks of Clerodendrum cyrtophyllum. Multi-gene phylogenetic analysis of 5.8S-ITS rDNA, nrSSU, EF-1α, and RPB1 gene loci also confirmed the distinctiveness of this new species.